Reading Books While Listening Music: Case Study To Students Of Universitas Negeri Semarang (Universitas Negeri Semarang, 2022)
Researchers conducted a case study on reading while listening music in Universitas Negeri Semarang students. The purpose of this study is to find out and explain what types of music students listen to while reading and to find out and explain how the functions of music that students listen to while reading. This study used Mix Method Research (MMR), which is a research method that combines qualitative and quantitative methods with a phenomenological approach. Data collection techniques used in this study were questionnaires and interviews. Data validity uses source triangulation. The results of this study indicate that the types of music that can be used as a medium to increase students' reading concentration are popular types of music, and also types of music with the same theme as the reading books they are reading. From the percentage, it can be concluded that music has an influence when it is listened to along with reading activities. The influence felt by respondents when listening to music together with reading activities is that it can make them comfortable, focus, and support the story or book they are reading.